ANALISIS FAKTOR DETERMINAN KEIKUTSERTAAN PETANI BERKELOMPOK, PENDAPATAN DAN PEMASARAN JERUK SIAM DI KABUPATEN JEMBER - Julian Adam Ridjal (University of Jember, 2008)
This objective of the study were to identify and analyze the factors influencing farmer in chosening to group or individual, knowing followedly in siam citrus earnings farmer group become higher and to know siam citrus marketing system from farmer by using approach SCP (Structure, Conduct and Performance). The Result of research indicate that factor mount amenity and education obtain;get capital have an effect on reality to farmer opportunity in chosening to team or individual for onfarm activity, while age factor, wide of farm, sum up family member, earnings per hectare, sum up tree, experience, amenity info of market price, amenity of onfarm information and have an effect on is not real to farmer opportunity in chosening to team or onfarm information and have an effect on is not real to farmer opportunity in chosening to team or individual for onfarm activity. Statistically was obtained that no earnings differencess mean between grouping farmer and individual farmer. There are three channel of siam citrus marketing, are : (1) farmer PP I (compiler merchant) PP II (consignor merchant)PBLK (market), (2) farmer of PP II, (3) farmer to PBLK ( market). Market tend to oligopoly and there is integration between farmer price (produsen) and the retail price (market-consumer). Level price of farmer less responsive to price change of market , so change price level of market is not at moment's notice transferred or level of farmer with same percentage. Others there was still imbalance distribution of marketing margin, profit and marketing cost, as well as the ratio of profit to marketing cost of the market actors. Key words : siam citrus earning, opportunity to farmer, structure-conduct-performance.